Slam: a Poesia Oral Como Signo de Afirmação Identitária E ressignificação Histórica de Mulheres Negras. - Vago, Fabrícia Bittencourt Pazinatto (2021)
It is proposed to expand the discussions about spoken poetry competitions events called slams, which are established as political and aesthetic spaces. In Brazil slams were born in poor city areas. The texts presented in the slams events are discursive productions that have grown as political practice and cultural resistance. The slammers use the poetry competition performance as a subversive possibility for not only identities building, but also for silences breaking, and assumption of a historically denied space. The research corpus is defined by texts produced by das Minas Slam and Nísia Slam young female writers that live in pheripheries areas of São Paulo and Espirito Santo states respectively. The research supports are based in intersectional black feminism studies from Brazilian Sueli Carneiro and the Americans bell hooks, Patricia Hill Collins and Angela Davis. The discriminatory systems were analyzed based on the intersectionality concept of race, gender, and class, sustained by Lélia Gonzalez and Kimberlé Crenshaw. The study aims is a qualitative research based on the exploratory method, because it covers bibliographical survey, interviews, field research, and literary corpus analysis. It finds and defends that it is socialy and literary important to enhance new epistomies talks and to put a spot in periphery poets placed in subalternity. By poetry creation in movements such as the slam, these woman manage to break silences and unveil historical invisibilities. By doing so, they resignify representations and resist to political alignment, building their identities and artictic productions based on their ESCREVIVÊNCIAS in cultural movements such as the slam.